Unveiling the Presence of Escherichia coli in Meatball Cart Traders' Tableware: A Comprehensive Analysis in Region X - Dwi Yunatiasri, Listy; Yudha, Redi (HIGIENE: Jurnal Kesehatan Lingkungan, 2024)
Mobile meatball cart traders, who operate through portable carts, face challenges in maintaining sanitation due to limited space and poor hygiene practices. Tableware cleanliness plays a crucial role in preventing the spread of disease-causing bacteria, particularly Escherichia coli (E. coli). This study aims to investigate the presence of E. coli in bowls used by meatball cart traders, assess the sanitation conditions of their facilities and environment, and evaluate the knowledge, attitudes, and behaviors of traders towards washing, drying, and storing cutlery techniques. This descriptive research includes laboratory analysis to determine the presence of E. coli in the bowls. The total sampling method was used, involving a population of 10 traders. The examination of ten bowl samples indicated 100% compliance with the quality standard for E. coli presence, as outlined in Regulation No. 1096/Per/VI/2011 issued by the Minister of Health of the Republic of Indonesia (0 or <1x101 CFU/cm2). Equipment observations revealed that 60% of the samples met the quality criteria, while 80% of the selling areas exhibited satisfactory sanitation levels. The behavior of meatball traders towards washing, drying, and storage techniques was classified as sufficient, with an average score of 65.45%. Trader attitudes were considered good, with an average score of 75.8%, while trader behavior was categorized as sufficient, with a score of 65.4545%. It is strongly recommended to prioritize cleanliness, particularly in maintaining the hygiene of cutlery and the selling environment.